Modelling studies of charged particle interactions for a space application - Aplin, K; Tarakanov, V (2004)
An electron emitter neutraliser to prevent spacecraft charging from the use of positive ion thrusters is under development at the Rutherford Appleton Laboratory. A particle-in-cell code, KARAT, has been used to simulate laboratory experiments, Laboratory test results have been successfully obtained with simulations, for model verification. Neutraliser-ion thruster interactions in space have also been modelled. An ion-propelled spacecraft rapidly charges to kilovolt potentials, which can be dissipated by an electron-emitting neutraliser. The effect of background particle concentrations on neutralisation has also been studied.